EKSPLORASI TEORETIS DAN PRAKTIS ASESMEN PEMBELAJARAN MENDALAM: WORKSHOP DI SMKS KESEHATAN BALI MEDIKA DENPASAR - Hermawan, I Made Surya; Ekayanti, Ni Wayan; Diarta, I Made; Kumara, Komang Ayu Shri Candrika; Saputra, Pande Putu Eka; Budiasih, Fitri Nursiam (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Recently, the policy of deep learning approaches has emerged as a key innovation in Indonesian education. In response, teachers must be adequately prepared, both theoretically and practically, to ensure meaningful implementation of this policy. This community engagement activity aimed to enhance the theoretical understanding and practical competence of teachers at SMKS Kesehatan Bali Medika Denpasar regarding assessment for deep learning. The activity was conducted through a workshop method, encompassing the delivery of theoretical concepts on deep learning assessment as well as the development of formative and summative assessment instruments. A total of 30 teachers participated in the workshop, guided by six facilitators from the Biology Education Study Program, Faculty of Teacher Training and Education, Universitas Mahasaraswati Denpasar. The outcomes of the activity were found to be effective. In terms of theoretical understanding, the participants’ presentations demonstrated a comprehensive grasp of assessment for deep learning, particularly in balancing formative and summative assessments and in promoting student involvement through learning feedback, self-assessment, and peer-assessment. In terms of practical competence, the teachers successfully developed problem-based assessment rubrics. A notable improvement was observed between the initial rubrics and those refined through collaborative discussion, particularly in the objectivity of the scoring categories, which shifted from potentially biased to more objective formulations. Despite these improvements in theoretical and practical aspects as targeted, continuous professional development remains essential to sustain and deepen teachers’ understanding amidst evolving educational policies. Furthermore, the development of summative assessment instruments must be expanded beyond problem-based rubrics to include observation checklists, project and product assessment rubrics, as well as portfolio evaluations.